Klaim Republik Rakyat China atas Zona Ekonomi Ekslusif Indonesia - Baadilla, Efie (Faculty of Law, Universitas Pattimura, 2020)
The South China Sea is a strategic marine area and contains both living and non-living natural resources. The purpose of this paper is to analyze China's claim to Indonesia's ZEE in the South China Sea, which is known to Indonesia as the North Natuna Sea. China's claim to the Nine dash line in the South China Sea has had an impact on Indonesia and several countries. The research method uses normative research with a statute approach and a conceptual approach. The results of his study show that the recent conflict between Indonesia and China in the South China Sea has brought about a new conflict between the two countries even though Indonesia has so far not considered a problem. In fact, the application of the nine dash line as Traditional fishing grounds was not known in UNCLOS 1982, but the concept known was Traditional fishing rights. Indonesia has sovereignty and sovereign rights over North Natuna waters based on UNCLOS, for this reason, Indonesia needs to continue to carry out exploitation and exploration activities, supervision and legal action to guarantee the sovereign rights of the State.